Good Practices Pemanfaatan Media Internet dan Media Sosial dalam Pembelajaran - Febriansyah, Muhammad Raihan; Iswan; Nomi, Ahmad Suryadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Learning media is very important as a means of describing information and the essence of the learning process. Learning media provides benefits so that students more quickly understand the essentials of learning objectives that have been well designed. In the current technology and information-based era, the development of media that supports technology-based or digital learning processes has been very massive. The aim of this study is to identify best practices in the use of technology and information used in learning media specifically related to the diversity of types of internet-based learning media that are already commonly used. The method used in this scientific work is qualitative analysis using literature review studies, namely collecting various sources of information from scientific journals, books, articles and so on. The results of this study are learning media using media. The internet and social media make it easier for educators to understand learning material better, besides that digital-based learning media can be studied repeatedly so that students understand the lesson material better. Types of internet-based learning media that have benefits for students include interactive multimedia, digital video and animation, podcasts, augmented reality and virtual reality, game based learning, and several other methods.